Uczniowskie kluby sportowe w Polsce w świetle obowiązujących uregulowań prawnych oraz orzecznictwa sądów powszechnych = Students sports clubs in Poland in the light of existing legislation and legal regulation of general court jurisdiction - Rejman, Aneta (Journal of Education, Health and Sport, 2015)
Rejman Aneta. Uczniowskie kluby sportowe w Polsce w świetle obowiązujących uregulowań prawnych oraz orzecznictwa sądów powszechnych = Students sports clubs in Poland in the light of existing legislation and legal regulation of general court jurisdiction. Journal of Education, Health and Sport. 2015;5(12):656-665. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44761 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A656-665 https://pbn.nauka.gov.pl/works/694794 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Rejman Aneta. Uczniowskie kluby sportowe w Polsce w świetle obowiązujących uregulowań prawnych oraz orzecznictwa sądów powszechnych = Students sports clubs in Poland in the light of existing legislation and legal regulation of general court jurisdiction. Quality in Sport 2015;1(4):54-62. eISSN 2450-3118. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.12.2015. Revised 25.12.2015. Accepted: 29.12.2015. Aneta Rejman Uniwersytet Rzeszowski Uczniowskie kluby sportowe w Polsce w świetle obowiązujących uregulowań prawnych oraz orzecznictwa sądów powszechnych Students sports clubs in Poland in the light of existing legislation and legal regulation of general court jurisdiction Streszczenie Artykuł poświęcony jest kwestiom związanym z tworzeniem i działalnością uczniowskich klubów sportowych (UKS) w Polsce w świetle obowiązujących przepisów i regulacji prawnych. Doświadczenie pokazuje, że wiele ważnych decyzji dotyczących sfery uczniowskich klubów sportowych jest często podejmowana niezgodnie w stosunku do obowiązującego prawa. Chodzi przede wszystkim o sprawy związane z prawidłowymi zapisami w klubowych statutach, wpisami w rejestrze, a także przeprowadzaniem imprez sportowych. Artykuł jest swego rodzaju próbą podsumowania dotychczasowego prawa w obszarze poruszanego problemu. Słowa kluczowe: uczniowskie kluby sportowe, orzecznictwo, sądy (powszechne i administracyjne) Summary This article is devoted to the issues related to creation and activities of school’s clubs in Poland in the light of existing legislation and legal regulation of an administrative and general court jurisdiction. It examines the legislation and legal regulation in relating to the operation of school sports clubs, especially under the current sport law from 2010. Experience shows that a number of important decisions concerning the sphere of student sports clubs are often made in against the applicable law, or are the subject of an irrelevant administrative decisions . It is all about matters related to the proper editing of the Statute of the club, the entry in the register or the conduct of sport events - which means that after the exhaustion of the instance may be appealed to the ordinary courts. This article is a kind of an attempt to summarize the existing law, ie. the relevant law as well as constantly updated court decisions - designed to indicate the accuracy of proceedings in matters relating to the establishment and the activities of student’s clubs. Keywords: school sports clubs, legal regulation, courts (general and administrative)